Uji aktivitas antibakteri ekstrak daun ceremai (Phyllanthus acidus (L.) Skeels) terhadap Staphylococcus aureus - Alya Nafis; Dia Septiani; Jekmal Malau (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Staphylococcus aureus is a bacterium capable of causing pneumonia. However, the frequent occurrence of antibiotic resistance necessitates the exploration of alternative plant-based antibiotics as natural antibacterial agents. This study aims to analyse the antibacterial activity and chemical compound classes in the ethanol and methanol extracts of Phyllanthus acidus (L.) Skeels leaves, commonly known as ceremai leaves, exhibit antibacterial properties. Chemical compound classes were determined using the TLC method. The 96% ethanol extract of ceremai leaves contained flavonoids, alkaloids, triterpenoids, steroids, and phenols. On the other hand, the methanol extract contained flavonoids, alkaloids, steroids, and phenols. The antibacterial activity was evaluated using the Kirby-Bauer agar diffusion method. The testing revealed that ethanol and methanol extracts of ceremai leaves at concentrations of 15%, 20%, 25%, 30%, 40%, and 50% exhibited antibacterial activity against Staphylococcus aureus bacteria. The 50% concentration showed the highest inhibition zone value, with the ethanol extract (96%) measuring 3.86 ± 0.11 mm and the methanol extract measuring 2.73 ± 0.24 mm falling into the weak category